The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Proceedings of the 2017 2nd International Conference on Automation, Mechanical Control and Computational Engineering (AMCCE 201 2017
DOI: 10.2991/amcce-17.2017.36
|View full text |Cite
|
Sign up to set email alerts
|

Improved Recommendation Sorting of Collaborative Filtering Algorithm

Abstract: Abstract. The traditional collaborative filtering algorithm has no overall quantitative understanding on users' preference. This paper proposes a collaborative filtering algorithm based on improved recommendation sorting. Based on the traditional collaborative filtering rating prediction, three kinds of weighted sorting strategies are proposed to recommendation list, which are based on the combination of users' preference vector and item quality. Experiments on the MovieLens data set show that, in the same rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Traditional recommendation models can only process specific information, which cannot meet the requirements of different types of users for product characteristics and personalisation at different times and in various application scenarios. This paper focuses on the useful data obtained during the modelling process of predicting audience behaviour based on mathematical expressions, and applying them to the algorithm to obtain the corresponding performance indicators [8]. After the results of the expected utility function, correlation error size and regression analysis, it is experimentally demonstrated that the recommendation model can solve many practical problems, improve the efficiency and accuracy of the recommendation when processing information, and the performance of the algorithm model is greatly improved.…”
Section: Mathematical Expression Recommendation Modelmentioning
confidence: 99%
“…Traditional recommendation models can only process specific information, which cannot meet the requirements of different types of users for product characteristics and personalisation at different times and in various application scenarios. This paper focuses on the useful data obtained during the modelling process of predicting audience behaviour based on mathematical expressions, and applying them to the algorithm to obtain the corresponding performance indicators [8]. After the results of the expected utility function, correlation error size and regression analysis, it is experimentally demonstrated that the recommendation model can solve many practical problems, improve the efficiency and accuracy of the recommendation when processing information, and the performance of the algorithm model is greatly improved.…”
Section: Mathematical Expression Recommendation Modelmentioning
confidence: 99%
“…The collaborative filtering recommendation algorithm is the earliest and well-applied recommendation algorithm, which is used primarily for preference prediction and item recommendation. By mining a specified user's historical behavior data, the algorithm analyzes the user's interest, finds other users with similar interest in the user set, synthesizes the evaluation of these related users on certain items, forms the system's preference prediction for the items, and finally recommends items with similar interest for the user [19], [20].…”
Section: Traditional Collaborative Filtering Algorithmmentioning
confidence: 99%